From journey to journey identity and nationhood in F. Sionil Jose's Po-on and Viajero - Espiritu, Belinda F. (2001)
This paper traces the problematics of identity and nationhood as the country undergoes the transition from the colonial state to the nation state in F. Sionil Jose's two novels, Po-on and Viajero. The analysis of the two novels is founded on the idea that identity is permanently recreated while having a traditional base and prospective orientation and that contradictions and ambivalences are inherent in the postcolonial subaltern state. An existential angle provides a new twist in the discourse on Filipino identity while the dispossessed section of the populace is given a voice and a role to play in nation-building.
Keywords: Sionil, Francisco Jose; Filipino novel